Interpersonal Communication in the Dimension of Self-Disclosure of Mother as a River Sand Miner in Nupabomba Village of Donggala Regency - Sumarni Zainuddin; Israwaty Suriady; Muhammad Wahid (Indonesian Journal of Multidisciplinary Science, 2021)
This research aims to (1) to identify and provide an overview related to the hard work of a mother as a river sand miner in meeting the needs of family life and (2) To identify and provide an overview related to the disclosure of a mother as a river sand miner in meeting the needs of family life in Hamlet III Pombaloya, Nupabomba Village. qualitative research methods with the purposive withdrawal of informants. The results showed that based on the flow of activities mothers as sand miners must first finish (a) homework starting from dawn by preparing breakfast and cleaning the house. Next (b) work from morning to night to mine sand in the river. The work is done for several reasons for survival and changing the fate conveyed in the dimension of self-disclosure, namely (a) daily eating needs, (b) the need for education, and (c) the need for medicine.